Effectiveness of the CinQASE Web Integrated Learning Model to Train Higher Order Thinking Skills - Rahmat Saifuddin Anwar; Abdul Salam; Surya Haryandi; Nur Farahwahidah Abdul Rahman (Universitas Lambung Mangkurat, 2023)
The lack of training in higher-order cognitive thinking skills in physics makes most students of class XI MIPA in a high school in Marabahan unable to solve problems that require the ability to analyze (C4) and evaluate (C5) well. This study was intended to describe the effectiveness of using the web-integrated CinQASE learning model to train higher-order thinking skills in the C4 and C5 domains. This study used the pre-experimental one-group pretest-posttest design. The efficacy of the web-integrated CinQASE learning model to train higher-order thinking skills is calculated with the eta-squared effect size for a paired sample t-test. In contrast, the description of students' achievement in higher-order thinking is viewed from the percentage of the average score of the student learning outcomes test on items that have C4 and C5 domains. The results showed that using the model had moderate effectiveness (η2 = 0.94) and helped train students’ ability to think at a higher level, as shown by an increase in students’ achievement in higher-level thinking in the good category. Thereby, the use of the web-integrated CinQASE learning model can supply considerable benefits in training students’ higher-order thinking skills. These results also write down a practical need for teachers and schools to implement learning approaches that use the potential of technology to enhance learners’ higher-order thinking skills in the 21st century.